PENDAMPINGAN IMPLEMENTASI SISTEM APLIKASI AKUNTANSI BERBASIS EXCEL PADA BUMDES DESA MAYANGAN KABUPATEN JEMBER - Risma Puteri Anggraeni; Vina Fauzia Kartika; Risa Habibatul Ma’rufah; Ovie Vernanda Rumman Firdaus; Dwi Wahid Fitrianto; Dessy Putri Andini (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
. Village-Owned Enterprises (BUMDes) have a strategic role in encouraging village economic independence, but many still face obstacles in managing financial administration professionally. BUMDes Mayangan Village is one example that still uses manual recording methods without a standardized financial reporting system. This community service activity aims to increase the capacity of BUMDes administrators in preparing simple accounting-based financial reports through assistance in implementing a Microsoft Excel-based accounting application system. The implementation method includes team provision, partner profiling, technical training, assistance in recording transactions, to finalizing financial reports. The results of the activity showed a significant increase in the understanding and technical abilities of administrators in recording and preparing financial reports in accordance with basic accounting principles. The Excel system implemented has proven to be effective, easy to use, and able to present financial reports such as balance sheets, profit and loss statements, and cash flows in a more accountable manner. This activity is expected to be replicated in other BUMDes as a model for village financial management based on appropriate technology.